The Use of Snakes and Ladder Game to Increase the Students’ Interest in Learning Mathematics - Maulidar; Indah Suryawati (Universitas Serambi Mekkah, 2024)
This research aims to increase students' interest in learning mathematics through the use of the snakes and ladders game in class V at SD 53 Banda Aceh. This research uses a quantitative approach, while the design used in this research is a Quasi Experimental Pretest-Posttest Control Group Design. Data was collected in this research by giving questionnaire questions to see students' interest in learning mathematics. Based on the analysis of the results of the questionnaire on students' interest in learning mathematics, pre-test and post-test scores, it was found that the normalized gain (N-Gain) of students' interest in learning mathematics had a value of Sig. (2-tailed) = 0.031. Because the Sig value. (2-tailed) < significance level (α = 0.05), so H0 is rejected and Ha is accepted. Thus, it can be concluded that there is a difference between the average N-Gain interest in learning mathematics for students who are taught using the snakes and ladders game and the average N-Gain interest in learning mathematics for students taught using conventional learning. If we look at the average N-Gain value of the experimental class and control class, it is found that the N-Gain value of the experimental class is higher than the control class, so it can be concluded that there is an increase in students' interest in learning mathematics which is taught through the use of the snakes and ladders game at SD 53 Banda Aceh.